Phytotoxic Terpenoids from Ligularia cymbulifera Roots - Chen, Jia; Zheng, Guowei; Zhang, Yu; Aisa, Haji A.; Hao, Xiao-Jiang (Frontiers in Plant Science, 2017)
Ligularia cymbulifera is one of the predominant species in the Hengduan Mountains, China, and has led to a decrease in the amount of forage grass in this area. However, little is known about the mechanism behind its predominance. In this study, two novel eremophilane sesquiterpenes, ligulacymirin A and B (1 and 2), together with seven other known terpenoids (3–9), were isolated from the roots of L. cymbulifera. The structures of 1 and 2 were determined by spectroscopic methods and single-crystal X-ray diffraction. Each compound showed phytotoxic activities against Arabidopsis thaliana, and each was detected and identified in rhizosphere soil by UHPLC-MS. Compound 3 was the most potent phytotoxin, showing remarkable inhibition against both seedling growth (EC50= 30.33 ± 0.94 μg/mL) and seed germination (EC50= 155.13 ± 0.52 μg/mL), with an average content in rhizosphere soil of 3.44 μg/g. These results indicate that terpenoids in L. cymbulifera roots might be released as phytotoxins in rhizosphere soil to interfere with neighboring plants.